Different roles of sex steroid hormones in the pathogenesis of vascular dysfunction and the development of cardiovascular disease in men and women - Atalić, Bruno (Array, 2009)
Abstract: In this review an overview of current literature on the topic of the relation between sex steroid hormones and cardiovascular diseases (CVDs) is presented. The influence of the mentioned hormones on the three levels has been analyzed: their interaction with the blood vessel receptors, their modulation of the vascular function, and finally their role in the pathogenesis of CVDs. This review is focused not only on already known facts of the protective role of estrogens and the inceptive role of testosterone, but attempts to give examples of their opposite effects on vascular function and development of CVDs